Haydn's symphonic forms essays in compositional logic - Haimo, Ethan 1950- (Clarendon Press, 1995)
Beyond what they show about the composer's formal thought and the individual works discussed, the analyses in the book also have a larger purpose: to argue in support of the idea that compositions cannot be analysed in a meaningful manner if the analysis is divorced from the work's historical context
Keywords: Haydn, Joseph <1732-1809> / Symphonies; Haydn, Joseph <1732-1809> -- Symphonies; Haydn, Joseph -- 1732-1809; Structuuranalyse; Symfonieën; Symphonies -- Analysis, appreciation; Sinfonie; Musikalische Form; Komposition -- Musik